Advances in the Molecular Pathogenesis and Targeted Therapy of Psoriasis - Shokoufa, Parivash; Aghaei , Mahsa (Galen Medical Journal, 2025)
Psoriasis, a chronic immune-mediated skin disorder affecting 2-3% of the global population, is driven by a complex interplay of immune dysregulation, keratinocyte dysfunction, and genetic/epigenetic alterations, with systemic comorbidities like psoriatic arthritis and cardiovascular disease amplifying its burden. Recent molecular insights, leveraging single-cell RNA sequencing and transcriptomics, have elucidated key pathogenic mechanisms, including GSDME-mediated pyroptosis, IL-23/IL-17 axis activation, YAP1-driven proliferation, and epigenetic modulation via miR-106a-5p and lncRNA MEG3. These findings have spurred targeted therapies: IL-17 inhibitors (e.g., secukinumab) achieve rapid histologic remission, IL-23 inhibitors (e.g., risankizumab) offer sustained efficacy, and novel approaches like hyperforin, Deu@Cal microneedles, and concentrated growth factor (CGF) target diverse pathways in preclinical and early clinical settings. However, challenges persist, including adverse events (e.g., paradoxical eczema, MACEs), treatment resistance (81% biologic switching), and gaps in personalization despite promising biomarkers (e.g., calprotectin, miR-106a-5p). Future directions emphasize multi-omics integration, novel agents, and combination therapies to overcome these hurdles, aiming to transform psoriasis management into a paradigm of precision medicine.